Protection of rural children's right to education in a state of COVID-19 health emergency in Zimbabwe - Moumouni, Guillaume (University of Pretoria, 2021)
Mini Dissertation ((LLM) Human Rights and Democratisation in Africa)--University of Pretoria, 2021.